Anti-Selective Organocatalytic Michael Addition between Phenylacetaldehyde and Nitrostyrene - Gandolfi Donadío, Lucía (2016)
Using the reaction between phenylacetaldehyde and nitrostyrene catalyzed by pyrrolidine as a simple model, we have studied the diastereochemical outcome of the organocatalytic Michael reactions between benzylic aldehydes and nitrostyrenes. We found that the anti adduct was obtained in high yield and diastereoselection as was demonstrated by the X-ray structure of the product. In situ NMR studies showed a different reaction pathway when compared to aliphatic aldehydes that yield the syn adduct as major isomer.